Promise of PET imaging in prostate cancer: improvement or waste of money?. Issue 1 (January 2020) - Morigi, Joshua James; Anderson, Jack; Fanti, Stefano
Abstract : Purpose of review: Prostate cancer is a high prevalence malignancy whose management is a major challenge for clinicians worldwide. Molecular imaging, and in particular PET with computed tomography (PET/CT), is increasingly gaining importance in the work up and management of all prostate cancer patients. PET/CT remains, however, an expensive imaging modality and currently not reimbursed. Recent findings: Although other PET tracers are available and have gained institutional recognition from regulatory agencies, prostate-specific membrane agents (PSMA)-based PET/CT tracers have demonstrated the highest sensitivity and specificity for prostate cancer, outperforming any other PET radioligand to date. Regardless of the clinical scenario (staging, biochemical recurrence, therapy response assessment in advanced prostate cancer) PSMA PET/CT scans have become common practice in countries allowing for use outside of controlled clinical trials because of the overwhelming evidence demonstrating the extremely high sensitivity of this imaging modality in identifying prostate cancer lesions. This evidence can make PSMA PET/CT appealing for clinicians and lead to unnecessary scanning with limited supporting evidence. Summary: Our aim is to provide an update on the most recent literature available on PET-based imaging for prostate cancer and particularly PSMA PET/CT, offering an expert opinion on the data collected to provide clinicians with guidance on appropriateness and efficacy of PET-based imaging, in order to maximize clinical benefits and avoid waste of resources.